2018
DOI: 10.1002/naaq.10026
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Formulated Feed for Juvenile Lake Sturgeon Based on Growth Performance and Nutrient Retention

Abstract: This study evaluated the potential of feeding formulated feed to juvenile Lake Sturgeon Acipenser fulvescens and determined the optimal feeding rate of a soft-moist feed on the growth performance and whole-body composition of the fish. Six feeding rates (% body weight [BW]/d) of the soft-moist feed were assigned to each of the 1-week feeding trials: 2%, 4%, 6%, 8%, 10%, and 12% BW/d for trial I; and 0.5%, 2%, 3.5%, 5%, 6.5%, and 8% BW/d for trial II. As reference diets, frozen bloodworms and a dry formulated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 41 publications
4
17
0
Order By: Relevance
“…Regardless of the fact that water temperature and statistical analysis influence the determination of an optimum feeding rate, the estimated optimum feeding rate generally decreases over increasing body size. Feeding rate studies in other cultured fish species have also been reported (Bu et al, ; Einen, Mørkøre, Rørå, & Thomassen, ; Eroldoğan et al, ; Hatlen, Helland, & Grisdale‐Helland, ; Hung, Conte, & Hallen, ; Lee et al, ; Lee, Zhao, et al, ; Ng, Lu, Hashim, & Ali, ; Storebakken, Hung, Calver, & Plisetskaya, ; Xu et al, ). The increased growth responding to the graded feeding rates tested in both of the current trials is agreeable to the previous findings reported within the same species and in other fish species.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Regardless of the fact that water temperature and statistical analysis influence the determination of an optimum feeding rate, the estimated optimum feeding rate generally decreases over increasing body size. Feeding rate studies in other cultured fish species have also been reported (Bu et al, ; Einen, Mørkøre, Rørå, & Thomassen, ; Eroldoğan et al, ; Hatlen, Helland, & Grisdale‐Helland, ; Hung, Conte, & Hallen, ; Lee et al, ; Lee, Zhao, et al, ; Ng, Lu, Hashim, & Ali, ; Storebakken, Hung, Calver, & Plisetskaya, ; Xu et al, ). The increased growth responding to the graded feeding rates tested in both of the current trials is agreeable to the previous findings reported within the same species and in other fish species.…”
Section: Resultsmentioning
confidence: 87%
“…Although a criticism was raised by Shearer () almost two decades ago for selection of an inappropriate model that results in an erroneous outcome (i.e., selection of a model that does not reflect the feeding rate–response relationship best, resulting in a less accurate estimate), very little attention has still been paid on a question of whether a model chosen by researchers best fits to a given data set. Recently, a very few studies that tested various regression models for the estimation of an OFR reported that the estimates were not identical, indicating that model performance of the tested models was variable (Lee, Haller, Fangue, Fadel, & Hung, ; Lee, Zhao, et al, ). Interestingly, the model, a quadratic broken‐line model, that has been rarely tested by fish nutritionists was turned out to be the best‐fit model among the tested models, including the one‐slope straight broken‐line model, two‐slope straight broken‐line model and quadratic model (Lee et al, ; Lee, Zhao, et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Lee et al. ). Natural diets have a high moisture content (up to 90%) and variable caloric levels making calculating feed rates to maximize growth and minimize waste difficult.…”
mentioning
confidence: 98%
“…The greatest challenges in Lake Sturgeon culture are the long transition times to adapt to changing diets and the transition from natural food sources to commercially developed feeds. No commercially developed formulated diet exists specifically to optimize growth of Lake Sturgeon, and natural diets have typically produced higher survival rates than formulated feeds (DiLauro et al 1998;Hung and Deng 2002;Bauman et al 2016;Lee et al 2018). Natural diets have a high moisture content (up to 90%) and variable caloric levels making calculating feed rates to maximize growth and minimize waste difficult.…”
mentioning
confidence: 99%